Mobile media and communication: A new field, or just a new journal? - Campbell, Scott W. (Mobile Media & Communication, 2013)
This journal represents a step forward in the development of mobile communication studies as a field. This field has been establishing itself through a number of other initiatives as well, including conferences, symposiums, edited books, listservs, and centers for research. Despite this momentum, little attention has been given to defining – and justifying – the field itself. This essay begins by questioning whether there really is, or should be, a distinct field of study for research and theory on mobile media and communication. I then proceed to address this question by highlighting themes in the literature that illustrate how mobile communication is distinct from other forms of mediated communication and information exchange, with correspondingly distinctive social consequences. The essay argues that there are indeed justifiable reasons for treating mobile communication studies as a field. However, like the technology itself, this field is – or at least should be – highly integrated with research and theory of media and communication more broadly.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMDUwMTU3OTEyNDU5NDk1